EMPLOYEE PERFORMANCE MODEL THROUGH JOB SATISFACTION: WORK ENVIRONMENT ANALYSIS (A STUDY OF HUMAN RESOURCE MANAGEMENT LITERATURE STUDIES) - Junaidi Junaidi (Dinasti International Journal of Education Management And Social Science, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence employee performance through the work environment mediated by job satisfaction, A Study of Human Resource Management Literature. The results of this research library are that: 1) the work environment affects employee job satisfaction; 2) the work environment affects employee performance; 3) job satisfaction has an effect on employee performance; and 4) the work environment through job satisfaction has an effect on employee performance.